Electronic Parking Terminal (TPE) Program Implementation In Balikpapan City - Rahmadiansyah; Muhammad Jamal; Jauchar B (Jurnal Ilmu Pemerintahan, 2021)
This study aims to describe and analyze the implementation of the Electronic Parking Terminal Program in Balikpapan and the impact of outcomes from the use of electronic parking terminals. This type of research is descriptive qualitative. The results showed that at the Preparation stage for the implementation of the TPE Program including Resources Commited and Extent of change envisioned, the two indicators had several deficiencies. facilities in the form of integrators to facilitate payments that have not been installed, and thirdly communication the lack of communication transmission carried out by the UPTD. The outcome of the implementation of the Terminal Parking program is the outcome of the impact of the electronic parking terminal program, including minimizing leakage of public roadside parking fees and the sustainability of illegal jukirs. public roadside parking fees of Rp. 112,500,000, in addition to that the smoothness of traffic is still not optimal during peak hours along Jalan A. Yani it feels crowded due to the many vehicles parking carelessly, apart from that PAD and public roadside parking fees do not make a significant and significant contribution with stagnant achievements below the percentage of 5% (very less) even though the contribution rate is very low but the existence of TPE has an impact on increasing public roadside parking fees with an increase from 2017 to 2018 of IDR 1,149,475,000.00, besides that the effectiveness is good with an average average achievement of 90% (effective). Viewed as a whole the implementation of the Electronic Parking Terminal program in the city of Balikpapan has not been effective and optimal.